2001
DOI: 10.1097/00061198-200108000-00012
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Additive Intraocular Pressure???Lowering Effect of Latanoprost and Dorzolamide When Added to Timolol in Patients With Open-angle Glaucoma or Ocular Hypertension: A Randomized, Open-label, Multicenter Study in Greece

Abstract: This study clearly showed that the additive diurnal intraocular pressure-lowering effect of latanoprost is superior to that of dorzolamide in patients treated with timolol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 34 publications
1
9
0
1
Order By: Relevance
“…In timolol-treated subjects, adjunctive latanoprost lowered IOP signif icantly more than adjunctive dorzolamide (−7.06 mmHg; 32% vs −4.44 mmHg; 20% for adjunctive latanoprost and dorzolamide respectively) after 3-months in one study 175 and more than adjunctive pilocarpine 2%, 3 times daily in another. 130,176,177 Addition of latanoprost to pilocarpine therapy does not appear to diminish uveoscleral outflow 178,179 but is instead additive, 178,[180][181][182][183] contrary to thoughts that ciliary muscle contraction with cholinergics hinders uveoscleral outflow.…”
Section: Adjunctive Therapymentioning
confidence: 88%
“…In timolol-treated subjects, adjunctive latanoprost lowered IOP signif icantly more than adjunctive dorzolamide (−7.06 mmHg; 32% vs −4.44 mmHg; 20% for adjunctive latanoprost and dorzolamide respectively) after 3-months in one study 175 and more than adjunctive pilocarpine 2%, 3 times daily in another. 130,176,177 Addition of latanoprost to pilocarpine therapy does not appear to diminish uveoscleral outflow 178,179 but is instead additive, 178,[180][181][182][183] contrary to thoughts that ciliary muscle contraction with cholinergics hinders uveoscleral outflow.…”
Section: Adjunctive Therapymentioning
confidence: 88%
“…Therefore, control of IOP was achieved during the two months of the clinical protocol, regardless of the period and sequence of study (F (4,192) =1.442, p=0.222). The efficacy in controlling IOP showed no statistical differences between the two groups (F (1,48) =0.1675, p=0.898) (Figure 2).…”
Section: Efficacymentioning
confidence: 97%
“…Prostaglandin analogues (PGA) are the most effective either alone or in combination with autacoids. The esterification of carboxylic acid in a PGF2α reduces the amount of medication required to decrease intraocular pressure (IOP) and so acts to reduce the side effects associated with the PGA [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Note that a total of 18 studies (2943 patients) were included in this MTC, 20,23,28,37,40,51,55,60,73,78,89,[91][92][93][94]98,107,109 as these were the only studies included in the SR extraction that reported sufficient data on mean and standard deviation in IOP.…”
Section: Trigger For Treatment Switch 2: Failure To Meet Iop Targetsmentioning
confidence: 99%